Peralihan Agama dan Kebebasan Berkeyakinan - Sulfinadia, Hamda (FOKUS Jurnal Kajian Keislaman dan Kemasyarakatan, 2018)
This paper takes the topic of religious freedom. Freedom of belief when faced with the principle of freedom of religion promoted by the declaration of human rights cause differences in public perception. The formulation of freedom of religion can be understood by choosing or embracing a religion, out of a religion and no religion is the scope of freedom of religion. This also affects the law and the provision of transitional religious sanctions contrary to the principle of religious freedom which will affect the violation of human rights. The existence of clash between two interests is the author interested in discussing it further.This research is library research (literature study), with normative approach. Data collection is done by recording, reviewing and reviewing all information obtained from primary and secondary data. After the data collection process is complete, data selection, data grouping, and description process is the compilation of data into a narrative text. Then the data is analyzed qualitatively to get the conclusion.This research produces: 1) There is a difference of opinion of scholars related to the issue of religious transition. The majority of religious scholars believe that the case of religious transition into the hudud finger. This is due to the definite and permanent form of punishment and there is no chance for the ruler to forgive him. Meanwhile, according to Hanafiyah incase this transition case of religion on takzir jarimah, the consequences of death penalty is fixed and permanent, but there is an opportunity for the ruler to forgive him and forgive him; 2) For the murder of transitional people in the shari'ah of Islam is the replacement of religion accompanied by war. The war in the Islamic Shari'ah is a major crime that includes one of the crimes that disrupt the security of the state and damage the existing system.